2015
DOI: 10.1016/j.jcrs.2014.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of position of near addition in an asymmetric refractive multifocal intraocular lens on quality of vision

Abstract: Positioning of the near add did not significantly affect objective or subjective visual function parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
0
10
1
1
Order By: Relevance
“…Characteristically this can be interpreted in the OPD as coma rather than simply an increase in spherical power in the near add. 21 This current study only found a significant increase in trefoil aberrations when comparing preoperative to postoperative which again may be inaccurate and due to the aforementioned problems. We therefore assessed the isolated effect of corneal astigmatism upon objective outcomes and patient satisfaction.…”
Section: Discussioncontrasting
confidence: 53%
“…Characteristically this can be interpreted in the OPD as coma rather than simply an increase in spherical power in the near add. 21 This current study only found a significant increase in trefoil aberrations when comparing preoperative to postoperative which again may be inaccurate and due to the aforementioned problems. We therefore assessed the isolated effect of corneal astigmatism upon objective outcomes and patient satisfaction.…”
Section: Discussioncontrasting
confidence: 53%
“…The + 1.5 D addition at the IOL plane is calculated to be + 1.06 D addition at the corneal plane. The optic is 6.0 mm in diameter and the overall length of the plate-haptic is 11.0 mm [ 7 9 ]. There was three toric models; T1 has 1.5 D toricity at the IOL plane and 1.04 D toricity at the corneal plane, T2 has 2.25 D and 1.56 D, and T3 has 3.0D and 2.08 D. The toric axis is fixed on the horizontal meridian of the IOL.…”
Section: Methodsmentioning
confidence: 99%
“…Так, в исследовании D. de Wit с соавт. [14] линза Lentis Mplus LS-312 устанавливалась с положением добавочного сегмента в нижненосовом квадранте (80 глаз, 40 пациентов) либо в верхневисочном квадранте (76 глаз, 38 пациентов). Во всех глазах была использована добавка +3.0 дптр., при этом не найдено различий в передаточной функции модуляции.…”
Section: A б влияние положения добавочного сегмента на остроту зренияunclassified